Testing process for small software development organizations - Rojas-Montes, Martha Lucía; Pino-Correa, Francisco José; Martínez, James Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Define a testing process in an organization can be valuable to the extent that it allows to: (i) increase product quality, (ii) facilitate the understanding and communication between team members, (iii) support the process improvement in a manner continous, (iv) and support the tasks' automatic execution. In this sense, this paper proposes a light weight process defined to guide and support the test process in small software development organizations. The proposed process incorporates functional testing techniques in order to setting the activities required to evaluate the software product's functionality from an organized and systematic manner, especially those having to do with the design and execution of tests. This process has been defined from the analysis of: (i) few existing testing process reference models, and (ii) different studies reviewed of the literature. This process has been successful used in a small software development company answer have observed that it can be useful and practical to perform tests of software product in this type of companies.